Recuperação de povoamento de Eucalyptus urophylla com aplicações de nitrogênio, potássio e calcário dolomítico - Valeri, Sérgio Valiengo [UNESP]; Ferreira, Manoel Evaristo [UNESP]; Martins, Maria Inez Espagnoli G. [UNESP]; Banzatto, David Ariovaldo [UNESP]; Alvarenga, Silvio Fernandes; Corradini, Lenine; Do Valle, Celina Ferraz (My University, 2001)
A plantation of Eucalyptus urophylla, established in 1984 on a Quartzpsamment Soil, at Altinopolis, São Paulo State, presented in 1989 an medium increment of the cylindrical volume of the trees of 13.97 m 3/ha/year and also showed deficiency symptoms of potassium, calcium and magnesium. At 4.33 years after planting were applied two doses of nitrogen (0 and 10 g/tree of N), potassium (0 and 20 g/tree of K 2O) and of dolomitic lime (0 and 500 g/tree), combined in a randomized block design arranged in a factorial way (2 × 2 × 2), with four replications, in order to study the recuperation of the tree growth rate. Evaluations of the trees growth were performed at 4.33, 5.67, 6.75 and at 7.58 years when cutting the plantation was done. The soil fertility and leaf concentrations of N, K, Ca and Mg were analyzed before and after the application of the treatments. The accumulation and distribution of biomass and of these nutrients in the tree components and in the litter, and the economic studies referring to the volumes of wood were also evaluated 7.58 years after planting. Potassium fertilization increased the mass of potassium in stemwood, stembark, foliage, fruits and litter, but the increase was greater in foliage and in the stembark. Liming increased the mass of magnesium in stemwood, stembark, foliage and litter, but the increase was greater in the litter. There was no isolated effect of nitrogen fertilization. The growth rate of trees was recovered with the potassium application, which increased the mean annual increment (MAI) of cylindrical volume from 13.85 m 3/ha/year without fertilizer to 16.82 m 3/ha/year. At 7.58 years after planting, there was observed an effect of the N x K x dolomitic lime interaction in the wood production. In the absence of nitrogen and dolomitic lime, the application of potassium increased the real volume of 43% and there was a gain of US$ 86.79/ha.
Recovery of a Eucalyptus urophylla plantation with nitrogen, potassium and dolomitic lime applications
Keywords: Economic gains; Eucalyptus urophylla; Fertilization; Nutrients; Productivity; Recovery; Biomass; Lime; Nitrogen; Potassium; Soil mechanics; Vegetation; Dolomitic lime; Plants (botany); Eucalyptus; Fertility; Plantations; Soil Mechanics